Legal protection for muslim women prisoners in Malaysia - Wan Roslili Majid (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2012)
This study examines the adequacy, or the lack of it, of legal protection for women prisoners from three different perspectives – Islamic law, International law and Malaysian law. The aim is to examine the consistency of these laws in addressing the rights of women prisoners and the compliance of the Malaysian authorities in the implementation of the provisions to protect the rights and interests of women prisoners. The study embarks on the premise that the current laws regulating the rights of women prisoners are inadequate to protect their interests. The study adopts a qualitative and comparative analysis when dealing with statutory laws as stipulated in the international and Malaysian laws. The provisions are meticulously selected on the merit of their relevancy to the context of the research in assessing the acceptable standard on legal protection for Muslim women prisoners' rights. Interviews with a hand-picked number of Muslim women prisoners from Kajang Women Prison were carried out to support the primary data. Inadvertently, the finding is also relevant to concurrently examine the implementation of Malaysian Prison Regulations, the only law that deals with the rights of prisoners in Malaysia; in terms of their strength and weaknesses. The study reveals that the laws - Islamic, international and Malaysian, all have adequate provisions governing women prisoners' rights and the protection of their well being contrary to the initial assumption of the research and much to the delight of the researcher. However, in the context of the Malaysian law, there are certain minor aspects where improvements are much needed such as the adoption of non-custodial measures for women prisoners with children and pregnant women as practiced under international law. In addition, wider engagement of NGOs should be encouraged to expedite the process of rehabilitation, reformation and skills training within the prison institution.